Upaya Mengembangkan Kemampuan Kognitif Anak dalam Mengenal Lambang Bilangan 1-10 Menggunakan Media Loose Part Melalui Kegiatan Bermain Variatif pada Anak Kelompok A TK Teratai Birayang - Nisa, Khairatun; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2022)
The background of this research is that children's ability to recognize number symbols 1-10 is still low due to the lack of varied teacher and media approaches. If this problem is not solved, it will have a low impact on knowing numbers and children will experience difficulties in their cognitive aspects. The purpose of this study was to find out the teacher's activities, children's activities, and their developmental achievements in the cognitive aspect in recognizing the number symbols 1-10 through various play activities using loose part media as a model in learning. This research was conducted using a qualitative research approach in the type of Classroom Action Research (CAR) with research subjects of class A children at Teratai Birayang Kindergarten, totaling 12 children. The type of research data is qualitative research where the data collection method is obtained from observation sheets of teacher and child activities while quantitative research methods for collecting data are obtained from children's learning outcomes sheets. Data analysis was descriptive qualitative and cross-tabulation with indicators of teacher activity achieving a score of ≥ 27 in the